2012
DOI: 10.1002/app.38372
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(methylphenylsiloxane)/phenylene‐silica hybrid material with interpenetrating networks and its performance as thermal resistant coating

Abstract: In this study, poly(methylphenylsiloxane) (PMPS) and phenylene‐silica based hybrid material with interpenetrating networks was prepared by a two‐step sol–gel process. Firstly, in the presence of H2SO4, the phenylene‐silica was formed as sol particles with high branching degree by cohydrolysis and condensation of phenylene‐bridged monomer, tetraethoxysilane (TEOS), and hexamethyldisiloxane (MM). Then, the intermediate transformed into gel framework in polymer matrix using alkali catalyst, in order to produce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…branching and cross-link density of polymeric materials [30,31]. The results obtained for these systems revealed that the applied coatings were able to provide barrier to the metal surface when tested in 3.5% NaCl solution.…”
Section: Electrochemical Propertiesmentioning
confidence: 90%
“…branching and cross-link density of polymeric materials [30,31]. The results obtained for these systems revealed that the applied coatings were able to provide barrier to the metal surface when tested in 3.5% NaCl solution.…”
Section: Electrochemical Propertiesmentioning
confidence: 90%
“…Also, TGA exhibited that the highest T 5% of blends exceeded 390°C, T max exceeded 500°C, and Y c exceeded 40%, which were all higher than those of pure PSi. Accordingly, the blended coating had outstanding heat resistance . Compared with thermal performance of the epoxy/methylphenyl silicone resin composites reported in recent literatures, thermal stability (the weight loss temperatures at 5 wt%) of blending composites only reached to 310°C to 380°C .…”
Section: Resultsmentioning
confidence: 77%
“…EIS is an established method for the evaluation of the corrosion protection of coatings but can also be used to assess film properties in general . The measurements of the impedance spectra and data analysis were performed with the same procedures as described in our previous article, where we demonstrated that EIS can be used to observe the progress of latex film formation.…”
Section: Resultsmentioning
confidence: 99%